Interactions of the anti-FcRn monoclonal antibody, rozanolixizumab, with Fcγ receptors and functional impact on immune cells in vitro - Omar S. Qureshi; Emma J. Sutton; Rosemary F. Bithell; Shauna M. West; Rona M. Cutler; Gillian McCluskey; Graham Craggs; Asher Maroof; Nicholas M. Barnes; David P. Humphreys; Stephen Rapecki; Bryan J. Smith; et al. (Taylor & Francis Group, 2024)
ABSTRACTRozanolixizumab is a humanized anti-neonatal Fc receptor (FcRn) monoclonal antibody (mAb) of the immunoglobulin G4 (IgG4) sub-class, currently in clinical development for the treatment of IgG autoantibody-driven diseases. This format is frequently used for therapeutic mAbs due to its intrinsic lower affinity for Fc gamma receptors (FcγR) and lack of C1q engagement. However, with growing evidence suggesting that no Fc-containing agent is truly "silent" in this respect, we explored the engagement of FcγRs and potential functional consequences with rozanolixizumab. In the study presented here, rozanolixizumab was shown to bind to FcγRs in both protein-protein and cell-based assays, and the kinetic data were broadly as expected based on published data for an IgG4 mAb. Rozanolixizumab was also able to mediate antibody bipolar bridging (ABB), a phenomenon that led to a reduction of labeled FcγRI from the surface of human macrophages in an FcRn-dependent manner. However, the presence of exogenous human IgG, even at low concentrations, was able to prevent both binding and ABB events. Furthermore, data from in vitro experiments using relevant human cell types that express both FcRn and FcγRI indicated no evidence for functional sequelae in relation to cellular activation events (e.g., intracellular signaling, cytokine production) upon either FcRn or FcγR binding of rozanolixizumab. These data raise important questions about whether therapeutic antagonistic mAbs like rozanolixizumab would necessarily engage FcγRs at doses typically administered to patients in the clinic, and hence challenge the relevance and interpretation of in vitro assays performed in the absence of competing IgG.